The Origin of Laurentia: Rae Craton as the Backstop for Proto-Laurentian Amalgamation by Slab Suction - Hoffman, Paul F. (Geoscience Canada, 2014)
Proto-Laurentia (i.e. pre-Grenvillian Laurentia) is an aggregate of six or more formerly independent Archean cratons that amalgamated convulsively in geons 19 and 18 (Orosirian Period), along with non-uniformly distributed areas of juvenile Paleoproterozoic crust. Subduction polarities and collision ages have been provisionally inferred between the major cratons (and some minor ones), most recently between the Rae and Hearne cratons. The oldest Orosirian collisions bound the Rae craton: 1.97 Ga (Taltson-Thelon orogen) in the west, and 1.92 Ga (Snowbird orogen) in the southeast. All other Orosirian collision ages in proto-Laurentia are < 1.88 Ga. The Rae craton was the upper plate during (asynchronous) plate convergence at its western and, tentatively, southeastern margins. Subsequent plate convergence in the Wopmay and Trans-Hudson orogens was complex, with the Rae craton embedded in the lower plate prior to the first accretion events (Calderian, Reindeer and Foxe orogenies), but in the upper plate during major subsequent convergence and terminal collisions, giving rise to the Great Bear and Cumberland magmatic arcs, respectively. The ‘orthoversion’ theory of supercontinental succession postulates that supercontinents amalgamate over geoidal lows within a meridional girdle of mantle downwellings, orthogonal to the lingering superswell at the site of the former supercontinent. If the downwelling nodes develop through positive feedback from the descent of cold oceanic slabs, then viscous traction should contribute to drawing the cratons together over the downwelling node. Viewed in this way, the Rae craton was the first to settle over the downwelling node and became the backstop for the other cratons that were drawn towards it by subduction. It was, literally, the origin of Laurentia. Whether the Rae craton was also the origin of Nuna, the hypothetical cogenetic supercontinent, depends on ages and subduction polarities of Orosirian sutures beyond proto-Laurentia. SOMMAIRE La proto-Laurentie (c.-à-d. la Laurentie pré-grenvillienne) est un agrégat d’au moins six cratons archéens indépendants qui se sont amalgamés convulsivement durant les géons 19 et 18 (Orosirien), le long de zones de croûtes juvéniles paléoprotérozoïques réparties de manière hétérogène. Les polarités de subduction et les âges de collision entre les grands cratons (et d’autres moins grands) ont été provisoirement déduits, le plus récemment entre le craton de Rae et le craton de Hearne. Les plus anciennes collisions orosiriennes ont soudé le craton de Rae : 1,97 Ga (orogène de Taltson-Thelon) dans l’ouest, et 1,92 Ga (orogène de Snowbird) dans le sud-est. Tous les autres âges de collision en proto-Laurentie sont inférieurs à 1,88 Ga. Le craton de Rae constituait la plaque supérieure durant la convergence de plaque (asynchrone) à sa marge ouest, et peut-être aussi à ses marges sud-est. La convergence de plaque subséquente dans les orogènes de Wopmay et Trans-Hudson a été complexe, le craton de Rae étant encastré dans la plaque inférieure avant les premiers événements d’accrétion (orogènes caldérienne, de Reindeer et de Fox), puis dans la plaque supérieure durant la grande convergence subséquente et les collisions terminales, ce qui a créé les arcs magmatiques de Great Bear et de Cumberland respectivement. La théorie de « l’orthoversion » de la succession des supercontinents présuppose que les supercontinents s’amalgament au-dessus de creux géoïdaux en deça d’une gaine méridienne de convections mantéliques descendantes, à angle droit d’un super-renflement persistant au site d’un ancien supercontinent. Si le nœud de convection descendante s’établit par rétroaction positive de la descente de plaques océaniques froides, la traction visqueuse devrait contribuer à entraîner les cratons ensembles au-dessus du nœud de convection descendante. Vu de cette façon, le craton de Rae a été le premier à s’établir au-dessus du nœud de convection descendante, ce qui en a fait la butée des autres cratons entraînés par la subduction. Littéralement, telle a été l’origine de la Laurentie. Quant à savoir si c’est le craton de Rae qui a été à l’origine de Nuna, cet hypothétique surpercontinent cogénétique, cela dépend des âges et des polarités de subduction des sutures orosiriennes au-delà de la proto-Laurentie.